Evaluation of the Area of Clean Ice and Debris Ice Glaciers in Salang Area of Parwan Province using Remote Sensing Technology - Ormal, Mustafa; ZAKIR, ZABIHULLAH; FOOSHANJI, WAZIR AHMAD (British journal of environmental studies, 2024)
The subject of my research paper is the Salang glaciers in Parwan province using GIS technology and remote sensing, the region has been researched by the mentioned technology, and within twenty years, from 1999 to 2019, the natural glaciers of the Salang area have been evaluated, and every five years a separate map has been arranged, the figures and data of each year have been calculated in separate tables. Since it is difficult to study the Salang glacier area closely, by using remote sensing technology, I have succeeded in evaluating its area, volume, and changes during the mentioned years. At first, it received its satellite images; later, it was corrected by the ENVI program, and the images were entered into the eCognation DEVELOPER and ArcGIS programs to reveal its bare and covered glacier areas.